(untitled) (Revista de História da UEG (REVHIST), 2022)
This article seeks to analyze the issue of understanding about the idea of ​​corruption, specifically in Portugal and Portuguese America and how this understanding reflected on the dynamics of the relationship between the metropolis and the colony, specifically in the context of the extraction of gold in Minas and in the region covered by the Companhia de Comercio de Pernambuco and Paraíba, during the Pombaline period. Thus, this article seeks to identify how such illegal practices had an impact on that society. Centering the analysis from the historiographical discussion on the subject, we also resorted in a secondary way to administrative correspondence found in the main documentary collections related to the colonial period, specifically the AHU and dictionaries produced in the period to support the analysis. Keywords: Corruption. Smuggling. Enslaved.